Pengaruh Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Kepuasan Kerja Anggota Kepolisian Di Satuan BRIMOB POLDA DIY - Hefrizon, Hefrizon (208-7721)
This study discusses the influence of transformational leadership to organizational culture, the influence of transformational leadership to job satisfaction and the influence of organizational culture to job satisfaction member of police environment. The populations in this study are all members of Brimobda Police Unit D.I. Yogyakarta totaling 860 people. While the number of samples is 12.5% of the population numbered 108 people. Data collected with the survey method is to provide a list of statements or questionnaires directly to the respondents. analysis data techniques in this study using SEM analysis (Structural Equation Modeling) which is operated through the 21st AMOS program.Â  From the research show that a significant positive effect of transformational leadership to organizational culture; transformational leadership has a significant positive effect to job satisfaction; organizational culture had no significant effect to job satisfaction;Keywords: transformational leadership, organization culture, employee satisfaction